VAP or poisoning; which one has more effect on patients’ outcomes in toxicological ICU? - Hashemian, Morteza; Kamalbeik, Sepideh; Haji Seyed Razi, Parmis; Barari, Behjat; Salimi, Alireza; Talaie, Haleh; Mahdavinejad, Arezou (Acta Biomedica Atenei Parmensis, 2015)
Background: Ventilator-associated pneumonia (VAP) is the main cause of acquired infections in ICUs. Every year, millions of people suffer from poisoning by various substances. Our aim was to determine the association between VAP incidence and different kinds of toxicity among Toxicological ICU (TICU) patients. Materials and Methods: Poisoned patients with diagnosis of VAP were enrolled to our retrospective study at TICU of Loghman Hakim Hospital. Data was collected through the medical records. The statistical analysis was performed with SPSS (version 16, Chicago, IL, USA). Results: Among 675 patients with MV > 48 h, 150 patients had the diagnosis of VAP. Mean age was 36.6 years. 74.7% were males. Intentional poisoning was 70.3%. The incidence of VAP was 22%. The higher incidence of VAP was recorded in anti depressants and opioid toxicities. The majority of bacterial isolates (81.3%) were multi drug resistance. MRSA accounted for 50.7% of VAP cases. Non survivors’ hospital length of stay (mean = 18.7days) was significantly higher than survivors (12.8). The hospital length of stay in VAP patients was highest in the Acinetobacter spp (mean > 20 days). Mortality rate of VAP cases was 18.6%. Conclusion: No specific association was detected between incidence of VAP and different kinds of toxicity, while Anti Depressants and opioids had high VAP incidence, in a Quarter of this population. It is noticeable that pesticide had the lowest incidence for its short hospitalization. In our TICU, MRSA and Acinetobacter spp were the main agents leading to VAP and prolonged ICU stay, respectively. (www.actabiomedica.it)